Improvement of ionic liquid properties for the absorption refrigeration cycle - Fuxin Yang; Qiang Zheng; Bangju Wang; Houzhang Tan; Xiaopo Wang (Energy Storage and Saving)
Ionic liquids (ILs), recognized as environmentally friendly green reagents, have good application prospects in many fields. However, their high viscosity has hindered their widespread application. Currently, an effective solution is to introduce a solvent as an additive. In this work, ethanol with different molar fractions was chosen to form working pairs with three ILs ([emim]BF4, [bmim]BF4 and [hmim]BF4), to reduce their viscosities. The densities and viscosities of the three working pairs were obtained in a temperature range of 293.15 to 338.15 K, thereby determining the thermal expansion coefficients. The effects of ethanol on the volumetric and viscometric characteristics of the three ILs are discussed. To further analyze the interactions between ethanol and the ILs, excess mole volume and viscosity deviations were introduced. The interactions between different molecules were stronger than those between the same molecules in the working pairs. This is the main reason why the addition of ethanol reduces the viscosity of the three ILs. Finally, the hard-sphere model was applied to predict the viscosities of the working pairs. Upon introducing an adjustable argument, the average absolute relative deviation of the prediction for the aforementioned three ILs decreased to 4.4%, 5.9%, and 5.0%, respectively.